2021
DOI: 10.1007/s00701-021-04931-y
|View full text |Cite
|
Sign up to set email alerts
|

Deep brain stimulation in patients on chronic antiplatelet or anticoagulation treatment

Abstract: Background In the aging society, many patients with movement disorders, pain syndromes, or psychiatric disorders who are candidates for deep brain stimulation (DBS) surgery suffer also from cardiovascular co-morbidities that require chronic antiplatelet or anticoagulation treatment. Because of a presumed increased risk of intracranial hemorrhage during or after surgery and limited knowledge about perioperative management, chronic antiplatelet or anticoagulation treatment often has been considered… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 41 publications
0
5
0
Order By: Relevance
“…Peri-operative antibiotic use is strongly associated with lower infection rate [ 6 ] and may have contributed to the relatively low infection rate in this study. Given the low infection rate, our study did not confirm potential risk factors reported in retrospective series including primary [ 7 ] or repeat implantation [ 8 ], operation time, body mass index, age, sex, diabetes [ 9 ], smoking, indication, capsulotomy, post-operative ICU admission [ 10 ], anti-thrombotic medication use [ 11 ], antibiotic wash, chlorhexidine skin preparation [ 12 ] (20), topical vancomycin powder [ 13 ], glycerol [ 14 ], or preoperative MRSA screening and treatment [ 15 ].…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…Peri-operative antibiotic use is strongly associated with lower infection rate [ 6 ] and may have contributed to the relatively low infection rate in this study. Given the low infection rate, our study did not confirm potential risk factors reported in retrospective series including primary [ 7 ] or repeat implantation [ 8 ], operation time, body mass index, age, sex, diabetes [ 9 ], smoking, indication, capsulotomy, post-operative ICU admission [ 10 ], anti-thrombotic medication use [ 11 ], antibiotic wash, chlorhexidine skin preparation [ 12 ] (20), topical vancomycin powder [ 13 ], glycerol [ 14 ], or preoperative MRSA screening and treatment [ 15 ].…”
Section: Discussionmentioning
confidence: 98%
“…However, there was a low haematoma rate in our series (2/427), similar to the rate of 0.4% in the WRAP-IT trial. A recent publication indicated a 1% haematoma rate for patients not on anti-thrombotic medication and a 5.9% haematoma rate for patients taking anti-thrombotic medication [ 11 ]. With increasing use of anti-thrombotic medication, there may be a role for assessing envelope use in this higher risk population.…”
Section: Discussionmentioning
confidence: 99%
“…All of the descriptive analyses were performed using the built-in Microsoft Excel functions [32]. The meta-analysis and meta-regression were performed via OpenMeta [Analyst], an open-source cross-platform software [33].…”
Section: Discussionmentioning
confidence: 99%
“…In addition, in the early postoperative phase (up to 72 h after surgery), hemorrhages may be leveraged by blood pressure derailments. Treatment recommendations include restarting of oral anticoagulation or antiplatelet therapy 14–28 days after DBS surgery [ 12 ] if necessary for comorbidities, reflecting normalization of the general postoperative bleeding risk after this period.…”
Section: Discussionmentioning
confidence: 99%